Strategie personalne w organizacjach międzynarodowych - Stor, Marzena (Strategies of human resources management in international organizations, 2007)
Managing complexities, diversities, contradictions, and changes makes one of the virtual problems that contemporary international corporations must face. This results in developing more and more advanced solutions that help to cope with such complicated reality. In this context the main goal of the article is to propose a classification of personnel strategies in international corporations with regard to their hierarchical and issuing relations with organizationwide strategies of international companies. To achieve this goal the author outlines the background for personnel strategy formulation in this kind of companies. This involves a few short presentations of a multidimensional profile of international company, the definition of strategic international human resources management, the concept of internal and external fit of personnel function as well as transnational trends in management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 187-201